Pros and Cons of the Constitutional Court's Decision Regarding the Position and Rights of Children Born Outside of Marriage According to Maqashid Shariah - Suhaeri, (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
This study examines the arguments of both proponents and opponents of the Constitutional Court's Number 46/PUUVIII/2010 decision regarding the legal status and rights of children born out of wedlock, using the maqashid syari’ah framework. Employing a qualitative method with a normative-descriptive approach, the research evaluates how each perspective aligns with the Islamic objective of preserving lineage (hifdz an-nasl). The findings reveal that while proponents base their stance on hajjiyah (complementary) needs, they tend to overlook the more fundamental dharuriyyah (essential) aspects. In contrast, opponents prioritize hifdz an-nasl at the dharuriyyah level, reflecting a stronger alignment with core Islamic legal principles. Therefore, the opposing arguments are considered more beneficial (maslahah) from a maqashid syari’ah standpoint. This research contributes to the theoretical development of maqashid-based legal reasoning in assessing state legal decisions affecting family and social structures.